Earthquake Detection IoT Prototype with Early Warning System Based on Vibration Sensor - Harahap, Nur Salimah; Purnama, Iwan; Rohani, Rohani (Sinkron : jurnal dan penelitian teknik informatika, 2025)
This research developed a prototype of an earthquake detector using a vibration sensor, integrated with a real-time early warning system through a buzzer and LCD display. The system is designed to detect vibrations that potentially indicate an earthquake in real time and to promptly provide alerts to the surrounding environment. The research followed a Research and Development (R&D) method using the waterfall model, which includes requirements analysis, system design, implementation, testing, and maintenance. The hardware components include Arduino Uno, a SW-420 vibration sensor, a buzzer, and an LCD, while the software utilizes Arduino IDE for coding. The test results show that the system successfully detects vibrations and displays real-time notifications, proving its effectiveness in early earthquake warning scenarios. This system is expected to support disaster mitigation efforts by offering a simple and affordable solution that can be implemented in vulnerable areas.